Development of Water Cycle Diorama Media to Improve Students' Critical Thinking Ability - Nasution, Nur Syabrina; Anas, Nirwana (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
Research purposes this is to produce a product in the form of a water cycle diorama media that is feasible, practical, and effective for increasing the ability to think critically. Methods applied in research This is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The population in this research was class V Mis Madinatussalam students, consisting of 30 students. Meanwhile, sampling in this study used a total sampling technique or used the entire population as the research sample. The data collection techniques used by researchers in this research were interviews, tests, and questionnaires. This research uses qualitative data through observation, interviews, and LKPD, while quantitative data is used through pre-test and post-test. In this research, the data obtained was analyzed qualitatively and quantitatively. Qualitative analysis is used to describe the product development process. Quantitative analysis is used to describe product quality assessments, response questionnaires, and test learning outcomes through effectiveness tests. The results of data analysis are used for product improvement. The use of diorama media at the time is feasible, practical, and effective for students in fifth-grade elementary school. The effectiveness of diorama media was measured using the N-gain test. The average pre-test and post-test was 0.41, with a percentage of 41% in the medium category. Future researchers can develop diorama media on different subjects to improve other 4C skills, such as creative thinking, collaboration, and communication.